Spatial frequencies in aesthetic website evaluations – explaining how ultra-rapid evaluations are formed - Thielsch, Meinald T.; Hirschfeld, Gerrit (Ergonomics)
This study investigates how aesthetic website evaluations, especially those formed after very brief presentations, depend on visual information that is encoded in low- or high-spatial frequencies. A total of 92 participants took part in the experiment. The study used a 3 × 3 mixed design in which presentation time (50, 500 and 10000 ms) and spatial filtering (low-pass filtered, high-pass filtered and unfiltered stimuli) were manipulated. First, we replicate prior results from online studies of high- and low-spatial frequencies. Second, we confirm a prediction from neurocognitive models that only low-spatial frequencies are relevant to aesthetic judgements in ultra-rapid presentation modes. Third, we demonstrate that stimulus repetitions lead to an overestimation of the importance of ultra-rapid stimulus presentations. Taken together, our results highlight the utility of neurocognitive models of visual processing to explain the rapid aesthetic evaluation of websites. Practitioner summary: Using neurocognitive models we present an approach to explain how aesthetic impressions are formed. We show that ultra-rapid judgements are connected with low- but not with high-spatial frequencies, which are neurologically processed in different visual pathways. Furthermore we identify possible methodological problems in previous studies of ultra-rapid website perception.